Rapid-Onset Heart Failure in a 44-Year-Old Man with Suspected Obstructive Sleep Apnea: A Missed Cardiometabolic Link - Rosita, Rita (Jurnal Ilmu Kedokteran Keluarga, 2026)
Background: Obstructive sleep apnea is increasingly recognized as a clinically important, yet still underdetected, contributor to cardiovascular disease. Recurrent upper-airway collapse during sleep causes intermittent hypoxemia, sleep fragmentation, sympathetic surges, marked swings in intrathoracic pressure, and downstream inflammatory and hemodynamic stress, all of which may accelerate cardiac remodeling and worsen heart failure.  Case presentation: We report the case of a 44-year-old Indonesian man who presented to primary care with a two-month history of progressive exertional dyspnea, orthopnea, paroxysmal nocturnal dyspnea, and fatigue. He had no known diabetes, smoking history, or previously diagnosed heart disease, but did have a paternal history of premature cardiac death. Examination revealed tachypnea, bibasal crackles, an S3 gallop, and mild hepatomegaly. Chest radiography showed cardiomegaly with pulmonary vascular congestion, and electrocardiography demonstrated left ventricular hypertrophy. His sleep history was notable for habitual snoring, fragmented sleep, short sleep duration, unrefreshing sleep, and daytime somnolence, raising strong suspicion for sleep-disordered breathing. Because of financial constraints, transthoracic echocardiography, natriuretic peptide testing, and formal sleep testing were deferred. He was treated empirically for newly recognized heart failure with congestion and improved clinically after one week of therapy.  Conclusion: This case highlights two practical messages for family medicine. First, sleep-disordered breathing should be considered in relatively young adults presenting with otherwise unexplained cardiopulmonary symptoms. Second, in low-resource settings, structured symptom inquiry and simple screening tools can identify high-risk patients and support timely referral, even when definitive testing is delayed.